A risk-based intervention approach to eliminate diabetes health disparities. Issue 5 (8th February 2018) - Calman, Neil S.; Hauser, Diane; Schussler, Lilli; Crump, Casey
Abstract : Type 2 diabetes plays a major role in racial/ethnic health disparities. We conducted the first study to examine whether multifaceted interventions targeting patients with poorly controlled diabetes (HgbA1c >9%) can reduce racial/ethnic disparities in diabetes control. Among 4595 patients with diabetes at a Federally Qualified Health Center in New York, a higher percentage of blacks (32%) and Hispanics/Latinos (32%) had poorly controlled diabetes than whites (25%) at baseline (prevalence ratio, 1.28; 95% CI, 1.14–1.43; P <0.001). After four years, this percentage was reduced in all groups (blacks, 21%; Hispanics/Latinos, 20%; whites, 20%; P <0.001 for each relative to baseline). Disparities in diabetes control also were significantly reduced (change in disparity relative to whites: blacks, P =0.03; Hispanics/Latinos, P =0.008). In this diverse population, interventions targeting patients with poorly controlled diabetes not only improved diabetes control in all racial/ethnic groups, but significantly reduced disparities. This approach warrants further testing and may help reduce disparities in other populations.